Stage-specific dynamic reorganization of genome topology shapes transcriptional neighborhoods in developing human retinal organoids - Qu, Zepeng; Batz, Zachary; Singh, Nivedita; Marchal, Claire; Swaroop, Anand (Cell reports (Cambridge), 2023)
We have generated a high-resolution Hi-C map of developing human retinal organoids to elucidate spatiotemporal dynamics of genomic architecture and its relationship with gene expression patterns. We demonstrate progressive stage-specific alterations in DNA topology and correlate these changes with transcription of cell-type-restricted gene markers during retinal differentiation. Temporal Hi-C reveals a shift toward A compartment for protein-coding genes and B compartment for non-coding RNAs, displaying high and low expression, respectively. Notably, retina-enriched genes are clustered near lost boundaries of topologically associated domains (TADs), and higher-order assemblages (i.e., TAD cliques) localize in active chromatin regions with binding sites for eye-field transcription factors. These genes gain chromatin contacts at their transcription start site as organoid differentiation proceeds. Our study provides a global view of chromatin architecture dynamics associated with diversification of cell types during retinal development and serves as a foundational resource for in-depth functional investigations of retinal developmental traits. [Display omitted] •Major change in 3D genome correlates with emergence of late-born retinal cell types•TAD boundaries and inter/intra-TAD interactions are dynamic and stage specific•Enhanced chromatin looping forms growing networks with retinal marker and TF genes•Genome topology of organoids progressively resembles that of the adult human retina Qu et al. use retinal organoids to measure the interplay between 3D genome organization and gene expression during the differentiation of a complex human neural tissue, showing topology changes at all levels in key retinal genes.